Specific heat of K0.71Na0.29Fe2As2 at very low temperatures - Reifenberger, Andreas; Hempel, Marius; Vogt, p; Aswartham, S.; Abdel-Hafiez, M.; Grinenko, V.; Wurmehl, S.; Drechsler, S.-L.; Fleischmann, Andreas; Enss, Christian; Klingeler, Rüdiger (Journal of low temperature physics, 2014)
A commercially available calorimeter has been used to investigate the specific heat of a high-quality K0.71Na0.29Fe2As2single crystal. The addenda heat capacity of the calorimeter is determined in the temperature range 0.02K ≤ T ≤. 0.54K. The data of the K0.71Na0.29Fe2As2 crystal imply the presence of a large T2 contribution to the specific heat which gives evidence of d-wave order parameter symmetry in the superconducting state. To improve the measurements, a novel design for a calorimeter with a paramagnetic temperature sensor is presented.